Building a small business that Warren Buffett would love - Brownlee, Adam, 1978- (Hoboken, N.J. : Wiley, 2012)
'The guide to making money the Warren Buffett wayThe book that presents the same fundamentals that Warren Buffet used to turn an initial $105,000 investment into a $40 billion fortune in a way the general reader can apply, Building A Small Business that Warren Buffett Would Love is a succinct, logical, and straightforward guide to financial success. Highlighting one simple message: that Warren Buffett successfully invests in great businesses with strong fundamentals, it argues that these fundamentals can be replicated in a small business to yield outstanding results. Offering a solution for people wanting to start a business to provide additional income in today's uncertain economy, and designed to help entrepreneurs build fundamentally sound, small businesses using Warren Buffett's business investment perspective, the book covers: An overview of Warren Buffett's investment methodology and how it applies to small businesses The details of the Buffett investment criteria--a consumer monopoly, strong earnings, low long term debt, and high ROE with the ability to reinvest earnings--and the application of these fundamentals to both start-up and existing small businesses An approach to building a small business that applies the well respected principles of Warren Buffett, the book presents an exciting new look at the steps to success that have been proven trustworthy by one of the richest men in the world'--
Machine generated contents note: Foreword Acknowledgments Introduction: Painting the Picture of the Ideal Business Chapter 1: Buffett and the Fundamental Business Perspective Chapter 2: The Importance of a Consumer Monopoly or Toll Bridge Chapter 3: Strong, Consistent and Growing Earnings Chapter 4: Emphasizing a High Return on Equity Chapter 5: Retained Earnings -- The Fuel for the Engine of Compounding Returns Chapter 6: The Tumor of Long-Term Debt Chapter 7: Keeping Up With the Joneses Chapter 8: With Healthy Net and Gross Margins Chapter 9: Building a Small Business That Warren Buffett Would Love -- Finishing the Landscape Epilogue Notes About the Author Index.
Keywords: Buffett, Warren; Investments